2015
DOI: 10.1088/1742-6596/632/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

The current status of orbital experiments for UHECR studies

Abstract: 4 A discussion of the Super-EUSO [48] and OWL [49] missions goes beyond the scope of the article. 5 See http://euso-balloon.lal.in2p3.fr

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…To eliminate the off-axis aberration an additional corrective element was introduced into the telescope system in form of a Fresnel lens in front of the photodetector. Two versions of the detector were developed: Baseline and Mylti-Eye Telescope System (METS) [9,10]. 1 1 EeV = 10 18 eV 2 KLYPVE is a Russian acronym for extreme energy cosmic rays.…”
Section: From Klypve To K-eusomentioning
confidence: 99%
“…To eliminate the off-axis aberration an additional corrective element was introduced into the telescope system in form of a Fresnel lens in front of the photodetector. Two versions of the detector were developed: Baseline and Mylti-Eye Telescope System (METS) [9,10]. 1 1 EeV = 10 18 eV 2 KLYPVE is a Russian acronym for extreme energy cosmic rays.…”
Section: From Klypve To K-eusomentioning
confidence: 99%
“…It was estimated by Olinto et al (2015) that with the annual exposure ∼ 5 × 10 4 km 2 sr above ∼ 60 EeV, JEM-EUSO will collect 429 events/yr, or about 2,145 events in 5 years. KLYPVE will have the annual exposure ∼ 1.2 × 10 4 km 2 sr above 50 EeV (Panasyuk et al 2015;Sakaki et al 2015) and thus will be able to detect more than 100 events every year of operation, and more than 600 events during its planned lifetime. It was concluded that with its huge annual exposure (almost an order of magnitude larger than that of the Pierre Auger Observatory) and the planned 5-year operation time, JEM-EUSO has excellent opportunities for confirming the existence of the TA hotspot at high confidence level.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…GRBs are believed to be sources of ultra-high energy cosmic rays (UHECR) (Waxman 2006;Abu-Zayyad et al 2012;Tokuno et al 2012;Abraham et al 2004;Panasyuk et al 2012;Takahashi 2009;Halzen and Klein 2010;Gorham et al 2009) and gravitational waves (GW) whose detection has been reported recently (Cutler and Thorne 2002;Abramovici et al 1992;Abbott et al 2016a), and is a prime example of multi-messenger astronomy. The rapid-response in the observation of electromagnetic counterparts to GW (Abbott et al 2016b) is important to obtain the rich information in physical processes of GRBs giving rise to each messenger and the time delay between them.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…GRBs are potential candidates of the next generation cosmological standard candles (Lipunov et al 2001;Amati et al 2008;Ghirlanda et al 2006;Panaitescu and Vestrand 2008); and they are also prime examples for multimessenger astrophysical observation because their direct photon measurements can be augmented through observations of the air showers that result from the entry of their ultra-highenergy cosmic ray (UHECR) particles into the atmosphere (e.g. TA (Abu-Zayyad et al 2012;Tokuno et al 2012), Auger (Abraham et al 2004), TUS (Panasyuk et al 2015), JEM-EUSO (Takahashi 2009)), of neutrinos (e.g. ICECUBE (Halzen and Klein 2010), ANITA (Gorham et al 2009)), and searches for GW (e.g.…”
Section: Introductionmentioning
confidence: 99%